TOD Concept among Architecture Graduates - Lutfi Prayogi (Department of Architecture Universitas Muhammadiyah Jakarta, 2018)
Transit-oriented development (TOD) is a topic that is currently much discussed by architects. Besides discussed by architects, TOD is also much considered by people of various disciplines, such as urban designer, urban planner, property developer, policy developer, etc. The TOD concept understood by architects may be different from the one understood by people of other disciplines. This article compares the TOD concept followed by (candidates of) architecture graduates with the TOD concept that is discussed by people of different disciplines. This article examines the TOD concept that is understood and applied to the architectural design of three architecture graduate candidates with the state of the art of the TOD concept. The comparison is carried out through direct observation of the architectural designing process of the three candidates and reading of the articles written by the candidates recording and summarizing their designing process and the rationales of their designs. It is found that the candidates are very familiar with the regional physical design aspect of TOD (i.e., land-use, density and street network) but are not very familiar with other elements (i.e., residents’ mobility, built environment development staging, and transit and property market and development financing). While the candidates applied TOD principles on land-use, density, and street network in their designs, they did not apply TOD principles on the mentioned other aspects. This article shows the TOD concept as understood by architecture graduates and the understanding’s position within the state of the art of the TOD concept; this article may serve as the shared footing for people of various disciplines to plan and design TOD.